Phosphate Removal from Aqueous Solutions using Activated Carbon Derived from Nypa fruticans - Marysha Amelia; Faisal Abdullah; Abrar Muslim; Hesti Meilina; Saiful Saiful (Aceh International Journal of Science and Technology)
Nypa fruticans (NF) waste which includes the empty fruit bunches and shells (NFW), frond (NFF) and leaflets (NFL) composes primarily of hemicellulose, cellulose and lignin, shows great potential as a raw material for activated carbon (AC). This study investigated the removal of phosphate from aqueous solutions using activated carbon derived from Nypa fruticans. The NFW, NFF and NFL was pyrolyzed and physically activated in a tube furnace. FTIR analysis revealed that the NFW-AC, NFF-AC and NFL-AC exhibited functional groups such as chemical functional group O-H, C-O-C, C-O, C=O, C-O and C-H stretching in hemicellulose, cellulose and lignin, which were associated with phosphate (PO4³⁻) adsorption. Among these, the NFW-AC showed the lowest transmittance and higher pore density. Adsorption experiments indicated a rapid initial adsorption within the first 5 min, followed by minimal changes until equilibrium was reached at 30 min. The NFW-AC showed the best performance with the highest efficiency (40.05%) and capacity (85.85 mg/g). Adsorption kinetics for all activated carbon were better described by the pseudo-second-order model, with highest capacities of 60.606 mg/g and adsorption rates of 0.0235 g/mg·min attributed to NFW-AC. The adsorption isotherms followed the Langmuir mode, yielding capacities of 60.606 mg/g, 31.546 mg/g and 8.1967 mg/g for the NFW-AC, NFF-AC, and NFL-AC, respectively. These findings demonstrated the potential of Nypa fruticans-based activated carbon for phosphate adsorption